2006
DOI: 10.1507/endocrj.k06-034
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Analysis of the CLCNKB Gene in Japanese Patients with Classic Bartter Syndrome

Abstract: Abstract. Deletions or mutations in the gene encoding the basolateral chloride channel CLC-Kb (CLCNKB) cause classic Bartter syndrome (MIM 602023), which is characterized by hypokalemic metabolic alkalosis, hyperreninemic hyperaldosteronism and hypercalciura. These patients are usually diagnosed during infancy or childhood due to failure to thrive and growth retardation. The purpose of this study was to investigate the underlying mutations in Japanese patients with classic Bartter syndrome. Seven Japanese pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
12
1
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 23 publications
2
12
1
2
Order By: Relevance
“…Further investigation is required to elucidate precise mechanisms in DCT. The mutation: c.1830 G>A in CLCNKB seems to be a founder mutation in Japanese BS type 3 [20]. In comparison to the previous 2 Japanese cases with BS type 3 harbor same mutation having hypocalciuria [21], our case with normocalciuria seems to be contradictory.…”
Section: Discussioncontrasting
confidence: 49%
See 1 more Smart Citation
“…Further investigation is required to elucidate precise mechanisms in DCT. The mutation: c.1830 G>A in CLCNKB seems to be a founder mutation in Japanese BS type 3 [20]. In comparison to the previous 2 Japanese cases with BS type 3 harbor same mutation having hypocalciuria [21], our case with normocalciuria seems to be contradictory.…”
Section: Discussioncontrasting
confidence: 49%
“…The reason for this discrepancy may be affected with CRF, in which urinary calcium excretion is increased. Considering that our case appears to have late manifestation, the homozygous mutation does not accelerate clinical presentation than heterozygous mutation [20,21].…”
Section: Discussionmentioning
confidence: 65%
“…By contrast, several studies in more homogeneous type III BS populations [1113, 21, 22] showed that whole gene deletions, though observed, tended to be present in compound heterozygosity with point mutations. In particular, Bettinelli found 8 different point mutations and 4 gross deletions in a homogeneous population of mostly Italian patients (the complete deletion of the CLCNKB gene was only found in 23% of patients) [11].…”
Section: Discussionmentioning
confidence: 81%
“…Moreover, some previously reported cases possess only heterozygous mutations and another mutations were missing (8,10). Some of these cases may attributable to the methodological problem of direct sequencing.…”
mentioning
confidence: 99%